A STUDY OF ACADEMIC ACHIEVEMENT BASED ON SELF-CONCEPT DIMENSIONS AMONG SENIOR SECONDARY SCHOOL STUDENTS - Kour, Jagneet; Bhatia, Raino (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates how different aspects of self-concept relate to academic achievement among senior secondary school students. The self-concept dimensions studied include physical, social, temperamental, educational, moral, intellectual, and overall self-concept. A descriptive survey method was used, and data were collected from senior secondary students using a standardized self-concept questionnaire and academic scores. Statistical analysis, including t-tests and ANOVA, revealed no significant differences in academic achievement across different levels of self-concept. These findings suggest that self-concept alone may not significantly influence students’ academic performance. The study highlights the need to explore additional psychological, social, and environmental factors that affect learning outcomes.